Paradoxical Augmentation of Experimental Spondyloarthritis by RORC Inhibition in HLA-B27 Transgenic Rats - van Tok, Melissa N.; Mandour, Mohamed; Wahle, Joseph; Labadia, Mark E.; van de Sande, Marleen G. H.; Nabozny, Gerald; Baeten, Dominique L.; van Duivenvoorde, Leonie M. (Frontiers in Immunology, 2021)
Objective IL-17A plays a major role in the pathogenesis of spondyloarthritis (SpA). Here we assessed the impact of inhibition of RAR related orphan receptor-γ (RORC), the key transcription factor controlling IL-17 production, on experimental SpA in HLA-B27 transgenic (tg) rats. Methods Experimental SpA was induced by immunization of HLA-B27 tg rats with heat-inactivated Mycobacterium tuberculosis. Splenocytes obtained at day 7, 14 and 21 after immunization were restimulated ex vivo to assess the induction of pro-inflammatory cytokines. Rats were then prophylactically treated with a RORC inhibitor versus vehicle control. The biologic effect of RORC inhibition was assessed by pro-inflammatory cytokine expression in draining lymph nodes. Arthritis and spondylitis were monitored clinically, and the degree of peripheral and axial inflammation, destruction and new bone formation was confirmed by histology. Results Ex vivo mRNA and protein analyses revealed the rapid and selective induction of IL-17A and IL-22 production by a variety of lymphocyte subsets upon disease induction in HLA-B27 tg rats. Prophylactic RORC inhibition in vivo suppressed the expression of IL-17A, IL17F, and IL-22 without affecting the expression of other T helper cell subset related genes. This biological effect did not translate into clinical efficacy as RORC inhibition significantly accelerated the onset of arthritis and spondylitis, and aggravated the clinical severity of arthritis. This worsening of experimental SpA was confirmed by histopathological demonstration of increased inflammation, destruction, and new bone formation. Conclusion Despite a significant suppression of the IL-17 axis, RORC inhibitor treatment accelerates and aggravates experimental SpA in the HLA-B27 tg rat model.